Muscle mechanics and energetics in chronic ankle instability and copers during landing: Strategies for adaptive adjustments in locomotion pattern - Tianle Jie; Datao Xu; Huiyu Zhou; Yongyan Zhang; Minjun Liang; Julien S. Baker; Yaodong Gu (Heliyon)
Individuals with chronic ankle instability (CAI) and copers typically exhibited aberrant landing kinematics. Altered kinematics might lead to changes in muscle loading, potentially affecting the energy demand of locomotion. Understanding alterations in muscle mechanics and energetics during landing could enhance the rehabilitation program design. Therefore, the objective of this study was to explore the muscle mechanics and energetics of individuals with CAI, copers, and healthy controls during single leg jump landing. Three groups, CAI, copers, and healthy individuals (total n = 66), performed the landing task, and data on 3D motion capture, ground reaction force (GRF), and muscle activation were simultaneously collected. A musculoskeletal model was applied to estimate muscle force and mechanical power. Compared to healthy groups, individuals with CAI showed increased peak muscle forces in the gluteus maximus (p < 0.001), gluteus medius (p < 0.001), vastus lateralis (p < 0.001), and peroneus longus (p < 0.001) during landing. Whereas copers exhibited higher peak muscle forces in the vastus lateralis (p < 0.05), medial gastrocnemius (p < 0.05), soleus (p < 0.05), and peroneus longus (p < 0.001). Additionally, negative mechanical power redistribution in CAI shifted from the ankle to the hip (p < 0.001), while copers exhibited a similar redistribution from the ankle to the knee (p < 0.05). This study suggested that both CAI and copers exhibit biomechanical modifications in proximal joints. Copers showed a novel landing strategy aimed for enhancing landing stability, but with the risk of ACL injury. The identified energy redistribution observed in both CAI and copers could potentially contribute to the recurrent ankle sprains. This research facilitates a better understanding of how muscle mechanics and energy demands influence the landing pattern in individuals with CAI and copers.